(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Pneumatosis Cystoides Intestinalis (PCI) is a rare disease characterized by presence of air-filled cysts in the gastrointestinal wall. The incidence of PCI is unknown as most of the patients are asymptomatic. Rarely, patients may experience symptoms secondary to the cysts. The pathogenesis of PCI is still unclear and as such many theories are proposed. Usually, no treatment is necessary for 85% of patients who are asymptomatic. Surgery may be required for complications. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 112-115